2024
DOI: 10.1021/acsnano.3c08628
|View full text |Cite
|
Sign up to set email alerts
|

Light-Emitting Plasmonic Tunneling Junctions: Current Status and Perspectives

Jibo Tang,
Quanbing Guo,
Yu Wu
et al.

Abstract: Quantum tunneling, in which electrons can tunnel through a finite potential barrier while simultaneously interacting with other matter excitation, is one of the most fascinating phenomena without classical correspondence. In an extremely thin metallic nanogap, the deep-subwavelength-confined plasmon modes can be directly excited by the inelastically tunneling electrons driven by an externally applied voltage. Light emission via inelastic tunneling possesses a great potential application for next-generation lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…Plasmonics has a wide range of applications in catalysis, sensing, subwavelength imaging, plasmon enhanced spectroscopy and lasing. Plasmons at interfaces can be excited not only by photons but also by high energy electrons in transmission electron microscopy (TEM) or low energy tunneling electrons in scanning tunneling microscopy and metal–insulator–metal (MIM) tunnel junctions via inelastic tunneling (IET) which may find applications as nanoscale light sources, data processing devices, or integrated optical circuits. Plasmonic molecular junctions are interesting for in operando single-molecule Raman spectroscopy, , controlled plasmonic grafting of molecular junctions, and hot carrier generation. We have shown that the generated plasmons can be controlled at the molecular level, where orientation of the molecules modulates polarization, and the structure of the molecules determines intensity and the dynamics of the light emission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmonics has a wide range of applications in catalysis, sensing, subwavelength imaging, plasmon enhanced spectroscopy and lasing. Plasmons at interfaces can be excited not only by photons but also by high energy electrons in transmission electron microscopy (TEM) or low energy tunneling electrons in scanning tunneling microscopy and metal–insulator–metal (MIM) tunnel junctions via inelastic tunneling (IET) which may find applications as nanoscale light sources, data processing devices, or integrated optical circuits. Plasmonic molecular junctions are interesting for in operando single-molecule Raman spectroscopy, , controlled plasmonic grafting of molecular junctions, and hot carrier generation. We have shown that the generated plasmons can be controlled at the molecular level, where orientation of the molecules modulates polarization, and the structure of the molecules determines intensity and the dynamics of the light emission.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, for plasmon excitation by tunneling electrons, the energy of the photons ( hv ) that escapes the junction should not be higher than the energy provided by the bias V across the junction following the quantum cutoff law given by eq h v e V where h is Planck’s constant, v is the frequency of the photon, and e is the elementary charge. Indeed, most studies report cutoff photon energies E c ≈ eV , but exceptions with E c > eV , or E c < eV , have also been observed. The underlying mechanisms that cause these deviations are not fully disclosed.…”
Section: Introductionmentioning
confidence: 99%
“…Compact and broadband light sources play a pivotal role in various applications, including optical communication, on-chip optical interconnection, and integrated optoelectronics [1][2][3][4]. Despite the early discovery of light emission via inelastic tunneling (LEIT) in the 1970s [5,6], its practical viability has been hindered by the low electron-photon conversion efficiency and the low device stability [7][8][9][10][11][12]. Recent advancements, particularly since 2015, have seen a transformative improvement in LEIT efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Under a small external electrical bias (<2 V), the inelastic electron tunnelling (IET) inside tunnel junctions could drive the electrical excitation of surface plasmons on noble metal electrodes, leading to tunnel junction light sources with small footprints and ultrafast response speeds . This tunnelling-based light emission has the potential to be used as a nanoscale light source for applications such as subnanometer probes for light-matter interactions, , electrically driven optical antennas and plasmonic circuits. , To realize the above applications, tunnel junctions are usually formed in different fashions ranging from scanning tunnelling microscopy (STM) junctions, to metal–insulator–metal (MIM) tunnel junctions, or molecular tunnel junctions (MTJ). Although many exciting works have been demonstrated in improving the electron-to-photon coupling efficiency and coupling these tunnelling-based light sources to optical waveguides, so far most tunnel junction devices still suffer from low yield and nonuniform emission, as the quantum tunnelling is highly sensitive to the thickness or local defects of the tunnel barrier.…”
mentioning
confidence: 99%